N-Benzyl-N-ethylmorpholinium chloride - Bian, Yan-Jiang (International Union of Crystallography, 2008)
In the crystal structure of the title compound, C(13)H(20)NO(+)·Cl(−), the morpholine ring is in a chair conformation and the molecules are linked by weak intermolecular C—H⋯Cl hydrogen bonding.